Incidence and determinants of maternal sepsis in Ghana in the midst of a pandemic - Charles Lwanga Noora; Adom Manu; Adolphina Addo-Lartey; Abdul Gafaru Mohammed; Donne Kofi Ameme; Ernest Kenu; Kwasi Torpey; Richard Adanu (BMC, 2022)
Abstract Background Despite being preventable, maternal sepsis continues to be a significant cause of death and morbidity, killing one in every four pregnant women globally. In Ghana, clinicians have observed that maternal sepsis is increasingly becoming a major contributor to maternal mortality. The lack of a consensus definition for maternal sepsis before 2017 created a gap in determining global and country-specific burden of maternal sepsis and its risk factors. This study determined the incidence and risk factors of clinically proven maternal sepsis in Ghana. Methods We conducted a prospective cohort study among 1476 randomly selected pregnant women in six health facilities in Ghana, from January to September 2020. Data were collected using primary data collection tools and reviewing the client's charts. We estimated the incidence rate of maternal sepsis per 1,000 pregnant women per person-week. Poisson regression model and the cox-proportional hazard regression model estimators were used to assess risk factors associated with the incidence of maternal sepsis at a 5% significance level. Results The overall incidence rate of maternal sepsis was 1.52 [95% CI: 1.20-1.96] per 1000 person-weeks. The majority of the participants entered the study at 10-13 weeks of gestation. The study participants' median body mass index score was 26.4 kgm−2 [22.9-30.1 kgm−2]. The risk of maternal sepsis was 4 times higher among women who developed urinary tract infection after delivery compared to those who did not (aHR: 4.38, 95% CI: 1.58-12.18, p < 0.05). Among those who developed caesarean section wound infection after delivery, the risk of maternal sepsis was 3 times higher compared to their counterparts (aHR: 3.77, 95% CI: 0.92-15.54, p < 0.05). Among pregnant women who showed any symptoms 14 days prior to exit from the study, the risk was significantly higher among pregnant women with a single symptom (aHR: 6.1, 95% CI: 2.42-15.21, p < 0.001) and those with two or more symptoms (aHR: 17.0, 95% CI: 4.19-69.00, p < 0.001). Conclusions Our findings show a low incidence of maternal sepsis in Ghana compared to most Low and Middle-Income Countries. Nonetheless, Maternal sepsis remains an important contributor to the overall maternal mortality burden. It is essential clinicians pay more attention to ensure early and prompt diagnosis. Factors significantly predicting maternal sepsis in Ghana were additional maternal morbidity, urinary tract infections, dysuria, and multiple symptoms. We recommend that Ghana Health Service should institute a surveillance system for maternal sepsis as a monthly reportable disease.